Design and construction of a near real-time advanced automated C-band scatterometer system - Lim, Ka-Sing; Koo, Voon Chet (EMW Publishing, 2008)
This paper presents the design and construction of a complete near real-time scatterometer system for in-situ measurement. The full polarimetric system is comprised of inexpensive Frequency Modulated Continuous Wave (FMCW) radar that is efficiently constructed from a combination of commercially available components and in-house fabricated circuitry. An automated advanced antenna positioning system (AAPS) is included in the development of the system, giving rise for a more practical measurement. The backscattering matrices of a 4 '' x 8 '' dihedral corner reflector are rotated and measured at different angles to provide different sets of polarimetric data. The backscattering matrices of 8 '' sphere, 12 '' sphere and 16.5 '' trihedral are also measured and the results are presented in this paper. In order to verify the effectiveness of the calibration technique, the results are compared with the theoretical values. Consideration on the challenges of measurement in outdoor environment is countered with external and internal calibration. As a result, the proposed scatterometer system has shown good correlation between measurement and theoretical results.